"Big big" gastrin release by the isolated islets of Langerhans incubated in vitro (Revista Española de Fisiología, 1980)
The immunoreactive form of gastrin released by the islets and some of the characteristics of this release have been studied.This gastrin released by the islets in the present experiments corresponds to what has been named "Big Big" gastrin in serum of patients with the Zollinger-Ellison syndrome, in normal human serum and in extracts of proximal jejunum.Most of the "Big Big" gastrin released from the islets corresponds to spontaneous release.